Toxoplasma gondii: isolation of tachyzoites rhoptries and incorporation into Iscom - Garcia, J. L.; Gennari, S. M.; Navarro, I. T.; Machado, R. Z.; Sinhorini, L. L. (Elsevier B.V., 2004)
Rhoptries have been isolated from Toxoplasma gondii tachyzoites by subcellular fractionation in isopynic density sucrose gradient. Five bands were observed, and transmission electron microscopy of these indicated that rhoptries were in band 3. This band had a density of 1.17g/cm(3). Fraction 1 had membrane structures of the parasite. Fraction 2 contained membranes and mitochondria (Fig. 1 B). Fraction 4 had mostly conoid structure (Fig. 2B) and fraction 5 showed ghosts. The electrophoretic and Western blotting analysis of the fractions indicated the presence of a number of proteins. Iscoms were constructed from band 3, which contained the rhoptry structures. Iscom showed a only protein incorporated of 55 kDa. Isolation of the parasite organelles has got in this work is necessary to identification, characterization, and function elucidation of the organelle proteins. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Toxoplasma gondii; protozoa; apicomplexan parasites; rhoptry isolation; rhoptry antigens; electron microscopy; Immunostimulating complex (Iscom); sodium dodecyl sulfate (SDS); Polyacrylamide gel electrophoresis (PAGE)